THE EFFECT OF LISTENING TO ENGLISH SONGS ON VOCABULARY DEVELOPMENT OF THE SECOND YEAR STUDENTS OF SMK TELKOM PEKANBARU - Ria Farhatun Nasia P; Fadly Azhar; Atni Prawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of listening to English songs on students’ vocabulary development in descriptive text. Many students face difficulties in developing English vocabulary due to limited word knowledge, and ineffective learning strategies. This study employed a quasi-experimental design with a non-equivalent control group design. The population consisted of second-year students of SMK Telkom Pekanbaru, with a sample of 41 students divided into an experimental class (21 students) and a control class (20 students). The experimental class was taught using English songs, while the control class used conventional methods. Data were collected through pre-test and post-test consisting of 35 multiple-choice questions that had been tested for validity and reliability (Cronbach's Alpha = 0.931 > 0.70). The data were analyzed using normality, homogeneity, and an independent sample t-test. The findings revealed a significant progress in the experimental group. The mean score increased from 71.76 (pre-test) to 86.86 (post-test), while the control group improved from 74.85 to 78.60. The t-test result showed that the significance value was 0.001 (<0.05), indicating that the alternative hypothesis was accepted. Listening to English songs has a significant positive effect on students’ vocabulary development. This method is recommended as an effective and engaging strategy in English language teaching.